Lipoic Acid-Coated Silver Nanoparticles: Biosafety Potential on the Vascular Microenvironment and Antibacterial Properties - Hajtuch, Justyna; Santos-Martinez, Maria Jose; Wojcik, Michal; Tomczyk, Ewelina; Jaskiewicz, Maciej; Kamysz, Wojciech; Narajczyk, Magdalena; Inkielewicz-Stepniak, Iwona (Frontiers in Pharmacology, 2022)
Purpose: To study and compare the antibacterial properties and the potential cytotoxic effects of commercially available uncoated silver nanoparticles (AgNPs) with lipoic acid coated silver nanoparticles (AgNPsLA) developed by our group. The antibacterial, cytotoxic and hemolytic properties of those NPs were assessed with the main objective of investigating if AgNPsLA could maintain their antibacterial properties while improving their biosafety profile over uncoated AgNPs within the blood vessel’s microenvironment. Methods: comercially available uncoated 2.6 nm AgNPs and 2.5 nm AgNPsLA synthesized and characterised as previously described by our group, were used in this study. Antimicrobial activity was assessed on a wide range of pathogens and expressed by minimal inhibitory concentrations (MIC). Assessment of cytotoxicity was carried out on human umbilical vein endothelial cells (HUVEC) using a MTT test. Detection of reactive oxygen species, cell apoptosis / necrosis in HUVEC and measurement of mitochondrial destabilization in HUVEC and platelets were performed by flow cytometry. The potential harmful effect of nanoparticles on red blood cells (RBCs) was investigated measuring haemoglobin and LDH released after exposure to NPs. Transmission electron microscopy was also used to determine if AgNPs and AgNPsLA could induced any ultrastructural changes on HUVEC cells and Staphylococcus aureus bacteria. Results: AgNPs and AgNPsLA had antimicrobial properties against pathogens associated to catheter-related bloodstream infections. AgNPs, in contrast to AgNPsLA, induced ROS production and apoptosis in HUVEC, ultrastructural changes in HUVEC and S. aureus, depolarization of mitochondrial membrane in HUVEC and platelets and also haemolysis. Conclusion: AgNPsLA synthesized by our group have antimicrobial activity and a better biosafety profile that uncoated AgNPs of similar size. Those observations are of critical importance for the future in vivo investigations and the potential application of AgNPsLA in medical devices for human use.